English Students’ Perspective in Participating the Praktisi Mengajar Program - Lisnani Ulfah; Isnaniah Isnaniah; Novi Dwi Yuliani (UMBanjarmasin, 2023)
The Teaching Practitioner Program is a flagship program of Merdeka Belajar Kampus Merdeka (MBKM). This research aims to examine students' perceptions regarding the importance of the program, its strengths and weaknesses, as well as how they adapt to it. This research is a qualitative study, conducted by distributing questionnaires to collect data from 15 English Education students at University of Nahdlatul Ulama Kalimantan Selatan who participated in the Teaching Practitioner Program during the academic year 2023/2024. The data were analyzed by distributing questionnaires to students then presented in the form of tables, bar charts, and percentages. The results of the study show that 72% of students consider this program important, 62% feel the program is adequate, 68% experience positive impacts, and 65% are able to adapt well to the program. Overall, the average positive rating is 67%, indicating that the Teaching Practitioner Program has a good impact on students.